Closure through Resilience: The Case of Prevent. (2nd April 2016) - Edwards, Phil
ABSTRACT: This article argues that systemic resilience in the face of terrorism is best conceptualized as a response to disruption of the political sphere, brought about by the forceful incursion of a would-be political actor. The ideological negotiation required to deal with political disruption is related to the "cycle of contention" model: engagement may take inclusive or exclusive forms, with consequences for the openness and hence the future resilience of the system. When the arguments used to support the British government's "Prevent" counterradicalization initiative are analyzed in these terms, the engagement is shown to be emphatically exclusive.